Effects of regular control of food colours content in meat products in Serbia. Issue 1 (October 2021) - Petronijevic, R B; Trbovic, D; Sefer, M
Abstract: Research of added food colours presence in meat products was carried out for a period of almost six years, as a continuance of previous study on market in Serbia. Improved method of high performance liquid chromatography was applied for identification and quantification od added colours in meat products. The colours were determined in variety of meat products, smoked meat and bacon, fermented sausages and heat-treated dry sausages, boiled sausages, cooked sausages, canned meat and meat meals, meat semiproducts and mechanically separated meat and, as a separated category, sea fish pastes, both from domestic market and from import. Over the 1400 products were analysed. The research results showed great improvement both in content of colours and labelling of products of meat products in Serbia.